John Chrysostom’s discourses on his first exile - Bonfiglio, E (2011)
The Sermo antequam iret in exilium and the Sermo cum iret in exsilium are two homilies allegedly pronounced by John Chrysostom in Constantinople at the end of summer 403, some time between the verdict of the Synod of the Oak and the day he left the city for his first exile. The aim of the thesis is to demonstrate that a new critical edition of these texts is needed before any study of their literary and historical value can be conducted. Chapter one sketches the historical background to which the text of the homilies refers and a concise survey about previous scholarship on the homilies on the first exile, from the time of Montfaucon’s edition until our days. The problem of the authenticity occupies the last part of the chapter. Chapter two investigates the history of the texts and takes into account both the direct and indirect traditions. It discusses the existence of double recensions hitherto unknown and provides the prefatory material for the new critical edition of recensio α of Sermo antequam iret in exilium and of the Sermo cum iret in exsilium. Chapter three comprises the Greek editions of the two homilies, as well as a provisional edition of the Latin version of the Sermo antequam iret in exilium. Chapter four is divided into two parts, each presenting a philological commentary on the text of the new editions. Systematic analysis of all the most important variant readings is offered. The final chapter summarizes the new findings and assesses the validity of previous criteria used for discerning the authenticity of the homilies on the exile.